Comparison of modelled- and remote sensing- derived daily snow line altitudes at Ulugh Muztagh, northern Tibetan Plateau - Marinka SPIESS; Eva HUINTJES; Christoph SCHNEIDER (Journal of Mountain Science, 2016)
The ice cap Ulugh Muztagh in the central Kunlun Shan at the northern fringe of the Tibetan Plateau is a very isolated region with arid cold conditions. No observational, meteorological or glaciological ground truth data is available. Using the Moderate-resolution Imaging Spectroradiometer (MODIS) Level 1 radiance Swath Data (MOD02QKM) with a spatial resolution of 250 m, transient snow lines during the months of July to September in 2001 to 2014 are derived. Results are used to calibrate the physical based Coupled Snowpack and Ice surface energy and Mass balance model (COSIMA). The model runs on a representative detail region of Ulugh Muztagh (UM) on a digital elevation model with the same spatial resolution as the MODIS bands. In the absence of field observations, the model is driven solely by dynamically downscaled global analysis data from the High Asia Refined analysis (HAR). We compare remote sensing derived and modelled mean regional transient snow line altitudes in the course of consecutive summer seasons in 2008 to 2010. The resulting snow line altitude (SLA) and annual equilibrium line altitude (ELA) proxy of both methods coincide very well in their interannual variability in accordance with interannual variability of climatic conditions. Since SLAs of both methods do not consistently agree on a daily basis a usage of remote sensing derived SLAs for model calibration in the absence of field observation data is only limitedly feasible for daily analysis. ELA approximation using the highest SLA at the end of ablation period may not be applied to UM because the negative winter mass balance (MB) is not reflected in the summer SLA. The study reveals moderate negative MB for UM throughout the modelling period. The mean regional MB of UM accounts for -523±410 mm w.e. a-1 in the modelling period. Hence UM seems not to belong to the area of the ‘Karakorum anomaly’ comprising a region of positive mass balances in recent years which has its centre presumably in the Western Kunlun Shan.